I (don't) owe you: Sovereign default and borrowing behavior - Dimitris Georgarakos; Alexander Popov (European Central Bank (ECB), 2024)
Using microdata from a U.S. household survey, we document that immigrants who lived through a sovereign default episode are 7% less likely to hold debt relative to otherwise similar immigrants who reside in the same U.S. state and come from the same foreign country but who did not experience a default. Conditional on holding debt, consumers in the former group borrow less and service lower debt burdens. The negative effect on borrowing behavior of having experienced a sovereign default increases with family size and declines with education. These findings highlight the role of personal experience in shaping households' financial decisions.
Keywords: G11; G51; H63; D83; 330; Sovereign default; household borrowing; experiences; immigrants